2023
DOI: 10.3389/fgene.2023.1167773
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia-induced oxidative stress and epigenetic regulation of ET-1 gene in endothelial cells

Abstract: Introduction: Hyperglycemia-induced endothelial dysfunction and the subsequent increase of oxidative stress could lead to aberrant regulation of various genes which are responsible for a range of functions. This study aims to find out how hyperglycemia affect oxidative stress and then the expression and methylation of endothelin 1 (ET-1) gene in in human umbilical vein endothelial cells (HUVEC).Methods: Cells were cultured in growth medium and exposed to low and high glucose concentrations to mimic normal and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Biswas et al reported the presence of hypomethylation in the proximal promoter and 5' UTR/ rst exon regions of EDN1 in high glucose-induced endothelial cells (HUVECs and HRECs) [60]. Another group reported about the hypomethylation of the promoter of ET-1 in the high glucose-induced HUVECs, though the difference with low glucose-treated HUVECs was not signi cant [61].…”
Section: Discussionmentioning
confidence: 99%
“…Biswas et al reported the presence of hypomethylation in the proximal promoter and 5' UTR/ rst exon regions of EDN1 in high glucose-induced endothelial cells (HUVECs and HRECs) [60]. Another group reported about the hypomethylation of the promoter of ET-1 in the high glucose-induced HUVECs, though the difference with low glucose-treated HUVECs was not signi cant [61].…”
Section: Discussionmentioning
confidence: 99%
“…Reactive oxygen species can damage cells and tissues, and stimulate inflammatory responses. Prolonged oxidative stress can disrupt the immune system, making it difficult to cope with inflammation ( 37 ). Finally, a high blood sugar level can impair the function of endothelial cells (inner lining of blood vessels), leading to vascular inflammation ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Even accounting for the papers which simply mention or review the use of DCFH2 or related probes, it seems likely that well over 6000 studies have utilized such probes. Despite well-known shortcomings, which have been repeatedly stressed by numerous authors, e.g., [5,6,8,9,13,19,23,24,27,30,54,55,[79][80][81][82][83][84][85][86][87][88][89], these probes continue to be widely recommended and used in many investigations, e.g., [90][91][92][93][94][95], including a recent study that attracted quite widespread press coverage [96]. There are three basic problems with this and similar 'leuco' dyes such as the chloromethyl analogue and other variants promoted by manufacturers; while DCFH2 is the best characterized, it seems likely that all exhibit many of the problems discussed below.…”
Section: Dichlorodihydrofluorescein (Dcfh2): By Far the Most Widely U...mentioning
confidence: 99%